The Effect of Simvastatin Use on Decreased Child-Pugh Score in Patients With Liver Cirrhosis - Nurifahmi, Rahmaningtyas; Ikawati, Zullies; Andayani, Tri Murti (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Simvastatin is an antihyperlipidemic known to have pleiotropic effects and is currently being used as adjunctive therapy in patients with liver cirrhosis. Mechanism of action of simvastatin is to increase the availability of nitric oxide (NO), improve hepatic microvascular dysfunction, and improve the degree of liver fibrosis. Long-term use of simvastatin is expected to improve the prognosis in patients with liver cirrhosis as shown by a decrease of Child-Pugh score. This study aims to determine the difference in the decrease in Child-Pugh scores between groups of patients who consumed simvastatin 10 mg, simvastatin 20 mg, and the group of patients who did not consume simvastatin. The method used in this study was analytic observational with a retrospective cohort design and was performed on outpatients diagnosed with liver cirrhosis at Dr. Sardjito Yogyakarta Hospital in the period January 2017 to December 2021. Child-Pugh scores were observed to decrease after 3 months of patients using simvastatin. A total of 40 samples were obtained consisting of 13 samples as the control group, 13 samples in the simvastatin 10 mg group, and 14 samples in the simvastatin 20 mg group. The difference of the decrease in Child-Pugh scores between 3 sample groups were analyzed using the Kruskal Wallis test. The result showed that there was no difference in the reduction in Child-Pugh scores between the group of patients not taking simvastatin, the group of patients taking simvastatin 10 mg, and the group of patients taking simvastatin 20 mg for 3 months (p=0.964). Further research with a larger sampel size is needed to confirm this result.